Decrease in behaviors associated with pain during catheter placement using a topical anesthetic formulation in cats - Chávez, Carol; Ubilla Carvajal, María José.; Goich, Mariela; Cañón Jones, Hernán Alberto.; Iturriaga, María Paz (Elsevier Inc., 2021)
In veterinary practice, peripheral catheter placement is very common. For some cats, this procedure can be painful and stressful. This study aimed to determine the effect of a topical anesthetic cream on pain reaction related to cephalic catheter placement in healthy, awake cats. 20 healthy cats, enrolled for ovariohysterectomy, were randomized to either a lidocaine 2.5%-prilocaine 2.5% cream or placebo cream group. In each group, the cream was applied for 30 minutes on a previously shaved skin overlying the cephalic vein and venipuncture was carried out using a 22-gauge catheter. The Cat Stress Score system was applied before venipuncture to ensure that the reaction observed was not associated with cat stress level. The behaviors associated with pain during venipuncture were also evaluated. All cats tolerated the application of the cream well. Cat Stress Score before venipuncture ranged from fully relaxed to very tense in both groups and no correlation was found between the behaviors associated with pain during venipuncture and cat stress level. 30 minutes of application time was effective in providing local anesthesia, with cats in the treatment group showing significantly fewer behaviors associated with pain than cats in the placebo group. The use of a topical anesthetic cream before peripheral catheter placement in non-emergency cases is feasible.
Keywords: Peripheral catheter placement lidocaine/prilocaine cream pain behavior cat stress; Peripheral catheter placement lidocaine; Prilocaine cream; Pain behavior; Cat stress